Clinical Consequences of Untreated Dental Caries among Primary School Children: A Cross-Sectional Study - Gudipaneni, Ravi Kumar (2022)
Objective: To evaluate the dental caries experience and clinical consequences of untreated dental caries (UDC) among primary school children of Al Jouf region, Saudi Arabia and to determine the correlation between dental caries experience and clinical consequences of UDC. Material and Methods: A 250 primary school children 6-7 years were recruited using systematic random sampling. The prevalence of dental caries in deciduous dentition was assessed by following WHO criteria using the dmft index and the clinical consequence of UDC was assessed with the pufa index. The pufa score was calculated cumulatively following the pufa diagnostic criteria. The Student’s t-test was used to equate the mean  dmft and  pufa scores between boys and girls. The correlation between the dmft and the pufa scores was evaluated using Pearson's correlation coefficient (r), and the p-value was set at 0.05 for statistical significance. Results: Out of which 154 (61.60%) boys and 94 (37.60%) were girls. The mean (SD) values of dmft for boys reported to be 5.37 (± 3.31) and for girls 6.35 (± 3.27), which was statistically significant with gender (p<0.001). Statistically, significant mean values of pufa were 1.20 (± 1.37) in boys and 1.71 (± 1.58) in  girls, respectively was observed (p<0.001). The Pearson correlation between dmft and pufa values showed  a highly significant positive correlation among dmft and pufa values (r= 0.635, p<0.001). Conclusion: The present study revealed that high caries prevalence and experience of the clinical consequences of UDC in the primary dentition, and there was a strong positive correlation between dmft and pufa score values.